Steep switching tunnel FET: a promise to extend the energy efficient roadmap for post-CMOS digital and analog/RF applications - Liu, Huichu; Datta, Suman; Narayanan, Vijaykrishnan (Proceedings of the 2013 International Symposium on Low Power Electronics and Design, 2013)
Steep switching Tunnel FETs (TFET) can extend the supply voltage scaling with improved energy efficiency for both digital and analog/RF application. In this paper, recent approaches on III-V Tunnel FET device design, prototype device demonstration, modeling techniques and performance evaluations for digital and analog/RF application are discussed and compared to CMOS technology. The impact of steep switching, uni-directional conduction and negative differential resistance characteristics are explored from circuit design perspective. Circuit-level implementation such as III-V TFET based Adder and SRAM design shows significant improvement on energy efficiency and power reduction below 0.3V for digital application. The analog/RF metric evaluation is presented including gm/Ids metric, temperature sensitivity, parasitic impact and noise performance. TFETs exhibit promising performance for high frequency, high sensitivity and ultra-low power RF rectifier application.